THE EFFECT OF INTEGRATING MOOC’S ON SAUDI FEMALE STUDENTS’ LISTENING ACHIEVEMENT - Freihat, Nasser; Al Zamil, Al Jawharah (European Scientific Journal, ESJ, 2014)
The purpose of this study was to investigate the effectiveness of a Massive Open Online Course (MOOC) on developing listening skills among Saudi EFL university students. To achieve this purpose, a listening was prepared and administered. Then, a MOOC was designed, programmed, and presented to the students to develop their listening skills. The sample of the research included forty level-one, English major students. They were randomly selected to be included in the experimental group (N=20) and the control group (N=20). Findings of the research revealed that the MOOC has been effective in the development of specific listening skills. The findings also revealed statistically significant differences between the post-test mean scores in all listening skills, namely, intensive, selective, and extensive which were in favor of the experimental group.